Evaluating Land Use Changes in Dhaka City’s Growing Urban Areas: : Causes and Consequences - Hoque, Sahela; Haque, Md. Anamul; Ratul, S M Salehin; Saika, Ummeh (The Jahangirnagar Review, 2025)
Urbanization has increased dramatically in recent years, with Dhaka City serving as a prominent example. It’s rapidly growing in size, presenting multifaceted challenges. Using a multidisciplinary approach, the study integrates GIS techniques, remote sensing analysis, and socio-economic surveys to assess the spatial transformations driven by urbanization. The findings aim to identify the key drivers of land use changes and evaluate their implications for urban planning and future growth in specific areas of the city. By offering insights into the dynamics of urban expansion, this research helps develop strategies for sustainably managing evolving land use patterns. Dhaka City’s rapid urban expansion has significantly changed land use patterns in its peri-urban areas, posing substantial obstacles to sustainable development.